Legal Analysis of Unlicensed Sand Mining Business Activities on Inherited Land - Noer Azizah, Afellia Danty; Jamin, Mohammad; Maharani, Andina Elok Puri (Fakultas Syariah INSURI Ponorogo, 2025)
This study aims to analyze the aspects of law and its impact on the environment, specifically in relation to the activity of mining sand that is conducted above land without official permission. Problems mainly occur in the study. This is how arrangement law affects activity mining, excavation in the ground, and the unexplored legacy​ , all of which require permission. This also impacts the environment created by the activity, as stated. Research this use method using a qualitative descriptive approach, incorporating interviews, field observations, and studies of literature, regulations, legislation, and related legal sources. Research results indicate that activity mining sand without permission contravenes Article 3 of Law Number 4 of 2009 concerning Mineral and Coal Mining, as every activity mining must obtain official permission in the form of an IUP or IPR. Activities categorized as illegal mining can result in charges of both administrative and criminal sanctions. From an environmental perspective, activities such as mining without permission cause various damages, including erosion, soil landslides, water pollution, damage to infrastructure and roads, and disturbance to the ecosystem of flora and fauna. Research confirms the importance of improving awareness of the law, community, and government supervision so that mining activities are conducted in accordance with the principles of sustainability and environmental protection, ensuring a healthy environment.